The Effects of Socioeconomic and Individual Characteristics on the Re-Migration Decision of Formal Workers in Surabaya - Aminullah, Brillian Akbar; Pratomo, Devanto Shasta; Susilo, Susilo (AIBPM Publisher, 2023)
The rise of migrant workers who migrate commuting is an interesting topic in this study. This study aims to determine the socioeconomic characteristics (education and income) of the probability of formal workers who are commuting to Surabaya and know the individual characteristics (marital status, age, number of family dependents, distance, and gender) to the probability of formal workers who are commuting in Surabaya. Using quantitative methods with logistic regression analysis is continued by looking for marginal effects values. In this study, income had a significant positive impact on the decision to commute to Surabaya, and the distance from Surabaya's region of origin to Surabaya had a significant positive effect on the decision to commute to the regular labor sector in Surabaya. I know to give. Education level had a significant positive impact on formal sector workers' decision to migrate to Surabaya, and marital status significantly impacted official sector workers' decision to migrate to Surabaya did not affect. For regular workers migrating to Surabaya, age significantly impacted the decision to commute to Surabaya. The number of family members did not significantly affect the decision to commute to Surabaya. This research is limited to the formal sector so that it can be developed again from the industry and regional reach.